Stunting prevention nutrition education through marine fish processing training in Sukabumi - Yoyoh Jubaedah; Neni Rohaeni; Nenden Rani Rinekasari; Heni Hernawati (Jurnal Abmas, 2025)
Stunting remains a serious nutritional problem in Indonesia, including in Sukabumi Regency, where the prevalence reaches 27%. In Cicareuh Village, Ciemas Subdistrict, there are still 14 cases of stunting among toddlers. In fact, this area has abundant marine fish resources that can be utilized as a source of high-quality animal protein. The low utilization of fish as a nutritious food source is due to the community's limited knowledge in processing it into varied and appealing products. This community service activity aimed to provide nutrition education and improve skills through training on the diversification of marine fish processing for mothers of toddlers. The implementation method used a learning-by-doing approach involving 20 participants (mothers of toddlers and PKK cadres). The material provided included nutrition counseling, demonstrations on the use of processing tools, and practical training on making fish balls, nuggets, and dim sum. The results of the activity demonstrated a significant increase in the knowledge and skills of the participants, as well as an interest in home-based culinary businesses, and the establishment of a network of cooperation with the village government. In conclusion, this program successfully improved nutrition literacy, supported stunting prevention, and created opportunities for family economic empowerment in coastal areas. Abstrak Stunting masih menjadi permasalahan gizi serius di Indonesia, termasuk di Kabupaten Sukabumi yang prevalensinya mencapai 27%. Desa Cicareuh, Kecamatan Ciemas, masih ditemukan 14 kasus stunting pada balita. Padahal, wilayah ini memiliki potensi sumber daya ikan laut yang melimpah dan dapat dimanfaatkan sebagai sumber protein hewani berkualitas tinggi. Rendahnya pemanfaatan ikan sebagai bahan pangan bergizi disebabkan oleh keterbatasan pengetahuan masyarakat dalam mengolahnya menjadi produk yang bervariasi dan menarik. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan edukasi gizi sekaligus meningkatkan keterampilan melalui pelatihan diversifikasi olahan ikan laut bagi ibu balita. Metode pelaksanaan menggunakan pendekatan learning by doing dengan melibatkan 20 peserta (ibu balita dan kader PKK). Materi yang diberikan meliputi penyuluhan gizi, demonstrasi penggunaan alat pengolahan, serta praktik pembuatan bakso, nugget, dan dimsum ikan. Hasil kegiatan menunjukkan adanya peningkatan signifikan dalam pengetahuan dan keterampilan peserta, muncul minat usaha kuliner rumah tangga, serta terbentuk jejaring kerja sama dengan pemerintah desa. Kesimpulannya, program ini berhasil meningkatkan literasi gizi, mendukung pencegahan stunting, serta membuka peluang pemberdayaan ekonomi keluarga di wilayah pesisir. Kata Kunci: diversifikasi ikan laut; edukasi gizi; stunting